The Effect of Online Reviews, Rating and Price on Online Hotel Booking Intention in Indonesia: The Moderating Role of Brand Image - Salsabila, Rania; Rubiyanti, Nurafni (Journal of International Conference Proceedings, 2023)
The growth of the internet in the current era shows a change from increasingly advanced technology to online media. Because there are so many good things about the internet, interaction marketing through internet media is growing very fast. Therefore, consumers are increasingly booking hotel rooms through online websites or online platforms. Many hotel bookers prefer and consider online hotel bookings through rating reviews and prices listed on the online application. Because of this, online reviews that have been generated by customers providing reviews about rooms and services, and thus their commentary information about hotel services in terms of quality, price, and level of service, are significantly more convincing to potential customers than advertisements for hotels. This research wants to know how online reviews, ratings, prices influence people's decision to book a hotel or not. We also look at how a hotel's brand image can strengthen the influence of people's decisions to book hotels. This research emphasizes the need for hotel managers to handle online customer reviews, ratings and prices, especially negative reviews, to take advantage of promotional opportunities. Considering that the hotel industry has become one of the industries that supports Indonesia to boost the country's economy and is one of the important industries in Indonesia, this study is expected to contribute and be able to encourage and drive other economic sectors.